The social media business equation [ using online connections to grow your bottom line - Orsburn, Eve Mayer (Course Technology, 2012)
Demonstrates how you and your organization can use social media to unlock exponential growth and immediate opportunities, no matter what your business size or industry. This book focuses on results-oriented strategies as the author dispels the myths and reveals the true secrets of using social media for amazing business growth